Optimizing Restaurant Tax Collection for Enhanced Regional Income and Fiscal Sustainability: A Case Study of Batam City - Debora Agnesia; Jionathan (Indonesia Accounting Research Journal, 2024)
This research delves into the analysis of restaurant tax collection as a pivotal component of revenue generation in Batam City, aiming to enhance the city's original regional income. Through a mixed-methods approach encompassing quantitative analysis, qualitative investigation, and stakeholder engagement, the study examines current tax collection practices, compliance rates, and their implications for economic development. The research elucidates notable trends, patterns, and challenges in tax collection, highlighting opportunities for improvement and policy recommendations. Findings underscore the importance of strengthening compliance mechanisms, modernizing administrative processes, targeting informal economy activities, implementing differential taxation policies, and enhancing collaboration between stakeholders. By leveraging these strategies, Batam City can optimize tax collection practices, maximize revenue generation potential, and foster sustainable economic growth. The conclusions drawn from this research provide valuable insights for policymakers, city officials, and stakeholders, guiding efforts towards achieving fiscal sustainability and advancing the socio-economic well-being of Batam City's residents.